Development and characterization of a long-acting nanoformulated abacavir prodrug. (August 2016) - Singh, Dhirender; McMillan, JoEllyn; Hilaire, James; Gautam, Nagsen; Palandri, Diana; Alnouti, Yazen; Gendelman, Howard E; Edagwa, Benson
Aim: A myristoylated abacavir (ABC) prodrug was synthesized to extend drug half-life and bioavailability.Methods: Myristoylated ABC (MABC) was made by esterifying myristic acid to the drug's 5-hydroxy-cyclopentene group. Chemical composition, antiretroviral activity, cell uptake and retention and cellular trafficking of free MABC and poloxamer nanoformulations of MABC were assessed by proton nuclear magnetic resonance and tested in human monocyte-derived macrophages. Pharmacokinetics of ABC and nanoformulated MABC were evaluated after intramuscular injection into mice. Results: MABC antiretroviral activity in monocyte-derived macrophages was comparable to native drug. Encasement of MABC into poloxamer nanoparticles extended drug bioavailability for 2 weeks.Conclusion: MABC synthesis and encasement in polymeric nanoformulations improved intracellular drug accumulation and demonstrate translational potential as part of a long-acting antiretroviral regimen.